The Application of Bokashi Fertilizer on the Growth of Cucumber Plants (Cucumis Sativus L.) - Sinaga, Febrita Damena; Mustamu, Novilda Elizabeth; Triyanto, Yudi; Zamzami, Lutfi Fadillah (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS, 2024)
The cucumber (Cucumis sativus L.) belongs to the Cucurbitaceae family (gourd plant), which is very popular with all levels of society. This research aimed to determine the proper use of bokashi fertilizer in the growth and production of cucumber plants (Cucumis sativus L). This research was carried out from  January 24, 2024, to March 2024, at Jl. Lintas Gunung Tua, Simatahari Village, Kotapinang District, North Sumatra, Indonesia a. This study used a non-factorial randomized block design (RAK) consisting of 1 factor, each factor consisting of 6 levels, namely T0:Control, T1: bokashi 200g, T2: bokashi 300g, T3: 400g, T4: 500g, T5: 600g, and analyzed with statistical analysis using SPSS. The research results show that the lowest dose of bokashi fertilizer was given at the control dose. At the same time, the best dose was at a dose of 600g/plant, which showed the highest response from each treatment